Fee Audit Sebagai Mediasi Pengaruh Kualitas Audit Terhadap Manajemen Laba (Analisis Jalur) - Widarti - (Jurnal Akuntansi, 2017)
Generally, people judge that KAP is included in the big four audit quality is better than non big four accounting firm. Auditors receive audit fee in exchange for professional services they provide to the company. Audit fee is the cost to the client for having had the audit services of an accounting firm. Is the high audit fees can be a mediating influence on earnings management audit kualias. By using linear regression analysis and the Path Analysis results showed that simultaneous audit quality and audit fee does not significantly affect earnings management with Value sig 0.130 p> level of sig 0,05.dan t test showed that the quality of the audit and the audit fee no significant effect on earnings management by each p value 0.089 and 0.690 sig is greater than 0.05. Based on the analysis path shows that audit fee can not be mediating the effect of audit quality on earnings management. It can be seen from the value of the t statistic - 3,288 <t table with a significant level of 0.05 is equal to 1,666 and the coefficient of mediation amounted to -343 958 not signifkan which means there is no mediation effect of audit fees in relation to audit quality on earnings management.